2022
DOI: 10.1111/cup.14320
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic acquired digital fibrokeratoma: A novel clinicopathologic entity

Abstract: A 26-year-old male presented with a 2-year history of a hyperkeratotic growth from the left index finger. Histopathology was consistent with an acquired digital fibrokeratoma with changes of a pleomorphic fibroma. Lesional cells were negative for CD34, Rb, and p53, and were positive for FXIIIa. We introduce the pleomorphic acquired digital fibrokeratoma as a novel clinicopathologic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…13 Kint et al 14 classified ADF into three types based on the clinical and histopathological features: type I (many collagen fiber bundles accompanied by a large amount of capillary hyperplasia), type II (many collagen bundles accompanied by obvious keratinization of the epidermis), and type III (flat to domeshaped tumor with few cellular components). Leo L. Wang et al 15 reported a case which histopathology was consistent with an acquired digital fibrokeratoma with changes of a pleomorphic fibroma. Lesional cells were negative for CD34, Rb, and p53, and were positive for FXIIIa.…”
Section: Dovepressmentioning
confidence: 97%
“…13 Kint et al 14 classified ADF into three types based on the clinical and histopathological features: type I (many collagen fiber bundles accompanied by a large amount of capillary hyperplasia), type II (many collagen bundles accompanied by obvious keratinization of the epidermis), and type III (flat to domeshaped tumor with few cellular components). Leo L. Wang et al 15 reported a case which histopathology was consistent with an acquired digital fibrokeratoma with changes of a pleomorphic fibroma. Lesional cells were negative for CD34, Rb, and p53, and were positive for FXIIIa.…”
Section: Dovepressmentioning
confidence: 97%